Environmental education: affirmative climate action in public administration students at ESPAM MFL (Research, Society and Development, 2025)
The aim of this research is to systematise the knowledge on environmental education and affirmative climate actions for the students of Public Administration of the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López (ESPAM MFL). Environmental education is key to foster climate engagement in public management. This study evaluated the impact of a training intervention on 147 students of Public Administration at ESPAM MFL, distributed among the first three levels of the course. Surveys were applied before and after a strategy based on the ECAS methodology, structured in four phases: educational content, awareness workshops, practical activities and critical reflection, carried out in person with teacher accompaniment. After the intervention, level 1N-C showed an increase in agreement on the importance of affirmative climate actions (from 51.43% to 74.37%), and on the concept of carbon footprint (from 43% to 58.99%). Likewise, 83.38% expressed a willingness to change their consumption habits, and 84.18% acknowledged personal responsibility towards conservation. Participation in environmental activities also increased, although it remains low at higher levels. The female gender had the highest percentage of agreement in almost all statements. It is concluded that the intervention substantially improved environmental understanding, perception and commitment, especially in the first levels. The application of active, contextualized and targeted methodologies proves to be effective in strengthening climate competencies in public education students.